Cadmium Interaction with Animal Cells (Springer International Publishing, 2018)
This book outlines the interaction of cadmium with the proteome and signalling molecules of mammalian cells. Chapters from expert contributors cover topics such as cadmium chemical biology, membrane receptors and transporters for cadmium and cadmium complexes, and targets of cadmium toxicity. Students and researchers working in bioinorganic chemistry will find this book an important account.